Development of Social Studies Curriculum Integrating Local and Global Contexts for Character Strengthening - Sukarni, Sukarni; Marsini, Marsini (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This research aims to develop a social studies curriculum that is integrated with local and global contexts to strengthen the character of the nation in elementary school students. The development was carried out in response to the need for a curriculum that is able to bridge the gap between local wisdom values and global issues within the framework of the Independent Curriculum and the Pancasila Student Profile. This study uses the Research and Development (R&D) method with the Borg & Gall model approach which is modified into six main stages: preliminary study, curriculum design, expert validation, revision, limited trial, and final revision. Product validity was tested by five experts, practicality was assessed by teachers and students, and effectiveness was measured through a pre-test and post-test design of one group on 41 students. The results showed that the curriculum developed was very valid (88.6%), practical (positive response of 92% of teachers and 88% of students), and statistically effective (t = 10.42; p < 0.05) in improving students' social behavior. These findings suggest that a local-global integrated social studies curriculum can be an innovative approach to character-based contextual learning.